2006
DOI: 10.1002/jca.20103
|View full text |Cite
|
Sign up to set email alerts
|

Combination regimen of methylprednisolone, IV immunoglobulin, and plasmapheresis early in the treatment of acute disseminated encephalomyelitis

Abstract: Acute disseminated encephalomyelitis (ADEM) is a demyelinating disease of the central nervous system that is associated with significant morbidity and mortality. Early recognition of the disease is of paramount importance; however, treatment options are limited because only case reports and small series are available in the literature. We report a case of a 42 year-old previously healthy man, whom we treated successfully with a combination regimen of methylprednisolone, IV immunoglobulin, and plasmapheresis ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…IVIG may have beneficial effects also as secondline therapy (class IV evidence) [149][150][151][152] especially in patients who could not receive or failed to respond to steroids (class IV evidence) [153][154][155] or in patients with peripheral nervous system involvement and steroid failure (class IV evidence). Alternatively combination therapy by steroids and IVIG (class IV evidence) [156][157][158][159][160][161] or steroids, IVIG and PE were suggested to have favourable effects especially if given early in the course of disease (class IV evidence) [162,163].…”
Section: Other Demyelinating Diseases Of Central Nervous Systemmentioning
confidence: 99%
“…IVIG may have beneficial effects also as secondline therapy (class IV evidence) [149][150][151][152] especially in patients who could not receive or failed to respond to steroids (class IV evidence) [153][154][155] or in patients with peripheral nervous system involvement and steroid failure (class IV evidence). Alternatively combination therapy by steroids and IVIG (class IV evidence) [156][157][158][159][160][161] or steroids, IVIG and PE were suggested to have favourable effects especially if given early in the course of disease (class IV evidence) [162,163].…”
Section: Other Demyelinating Diseases Of Central Nervous Systemmentioning
confidence: 99%
“…We examined 18 previously reported cases of treatment with plasmapheresis for ADEM cited in the English literature (10,12–21). These cases, including our own, were divided into two groups: a non‐steroid use group and a steroid‐failure group.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG therapy has shown promising results in uncontrolled investigations in ADEM but does not appear to be effective in MS [82][83][84][85][86][87][88][89][90][91]. A prospective non-randomized study in a cohort with ADEM found that involvement of both the central and peripheral nervous system (particularly in severe cases) predicted corticosteroid failure and benefit from IVIG [92].…”
Section: Acute Demyelinating Encephalomyelitis (Adem)/ Hyperacute Mulmentioning
confidence: 99%
“…IVIG as an adjunct to methylprednisolone has been evaluated in two randomized placebo-controlled trials for acute MS exacerbations enrolling a total of 95 patients with negative results [71,94]. Thus, IVIG may be considered in the treatment of ADEM, especially with peripheral nerve involvement, but does not appear to have a role in treatment of MS. A typical treatment regimen for ADEM consists of 0.4 g/kg/day daily or every other day for 3-5 doses, though single infusions of 2 g/kg have also been reported [82][83][84][85][86][87][88][89][90][91]95].…”
Section: Acute Demyelinating Encephalomyelitis (Adem)/ Hyperacute Mulmentioning
confidence: 99%